Relationship between risk stratification in emergency medical services, mortality and hospital length of stay - Gonçales, Paula Caroline; Pinto Júnior, Domingos; de Oliveira Salgado, Patrícia; Machado Chianca, Tânia Couto (Investigación y Educación en Enfermería, 2015)
Objective. To evaluate the relationship between risk stratification, mortality and hospital length of stay in emergency medical services. Methodology. A prospective cohort study that used the information in the ALERTÒ database of the HOSPUB to know the evolution of patients classified by nurses using the Manchester Risk Classification Triage System in the emergency medical services, of the Belo Horizonte Municipal Hospital - MG, Brazil. Results. 147,167 patients were analyzed, 5.9% were female. The most common risk classification was yellow (47.4%), followed by green (36.5%), orange (14.2%), blue (1.3%) and red (0.6%). The mean length of stay was less than one day in 95.4% of patients who were discharged from the hospital. Thirty percent of the patients classified as red, 2% of those classified as orange, and 0.3% of those classified as yellow died. There was direct a relationship between the severity of patient classification and the length of hospital stay. Conclusion. The risk classification system used by nurses in the hospital was a good predictor of death and hospital length of stay for patients admitted to the emergency medical services How to cite this article: Gonçales PC, Pinto DJ, Salgado PO, Chianca TCM. Relationship between risk stratification in emergency medical services, mortality and hospital length of stay. Invest Educ Enferm. 2015; 33(3):